Prevalence and Associated Factors of Hepatitis C in Self-introduced Substance Abusers - A Azizi; F Amirian; M Amirian (Tehran University of Medical Sciences, 2011)
Background & Aim: Considering the importance and high prevalence of hepatitis C among substance abusers, especially injection drug users, this study aimed to determine the prevalence and risk factors of Hepatitis C in self-introduced substance abusers in Farabi Addiction Hospital in Kermanshah in 2007. Methods & Materials: A total of 263 drug addicts' medical files were assessed during the study. Data (individual characteristics and results of serological tests) were gathered through the files. Data were analyzed by measuring frequency of correlation between the variables (Chi square test and logistic regression). Results: The mean age was 31.82±9.18 years; mean duration of drug abuse was 121.7±29.1 months for prisoners. From 263 individuals in the study, 22.1% were infected with HCV. The most common ways of substance use were injection (33.1%), and fumigation (32.3%). There was no history of imprisonment in 74.9% of individuals; and 52.9% had no history of drug injection. There was a history of physical or mental disorder in 25.5% of individuals. The Chi square statistical test showed significant relationship between HCV infection and substance abuse, and the way of consumption; and the t-test showed significant relationship with average daily consumption frequency. The highest relative risk ratio was for positive history of physical or mental illness (OR=8.33), and positive history of imprisonment (OR=5.94). Having multiple sexual partners increased the risk of being infected with the HCV (OR=2.92). Conclusion: The risk of HCV infection was independently increased with having a history of imprisonment, having multiple sexual partners, presence of physical or mental illnesses, and consumption methods in substance abusers.   Key words: addiction, addiction injection, prevalence of hepatitis C